The Pengaruh Pengungkapan Emisi Karbon dan Kinerja Lingkungan terhadap Nilai Perusahaan: (Studi pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022) - Ramdani, Kafi Ezra; Nugraha, Arie Apriadi (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
Energy sector companies must demonstrate environmental commitment by reducing carbon emissions to gain legitimacy and improve environmental performance. These two aspects affect investor perceptions and company value. This study aims to determine the effect of carbon emission disclosure and environmental performance on firm value. The research sample is energy sector companies listed on the Indonesia Stock Exchange in 2020-2022 (3 years) using purposive sampling technique. This research uses quantitative methods. The data used in this study are secondary data obtained from financial reports published by the Indonesia Stock Exchange (www.idx.com), sustainability reports published through the company's website, and PROPER books obtained from (proper.menlhk.go.id) and the hypothesis is tested using panel data regression analysis. The results of this study indicate that disclosure of carbon emissions has a positive effect on firm value. While environmental performance has no effect on firm value, disclosure of carbon emissions and environmental performance has a positive effect on firm value: Energy sector companies must demonstrate environmental commitment by reducing carbon emissions to gain legitimacy and improve environmental performance. These two aspects affect investor perceptions and company value. This study aims to determine the effect of carbon emission disclosure and environmental performance on firm value. The research sample is energy sector companies listed on the Indonesia Stock Exchange in 2020-2022 (3 years) using purposive sampling technique. This research uses quantitative methods. The data used in this study are secondary data obtained from financial reports published by the Indonesia Stock Exchange (www.idx.com), sustainability reports published through the company's website, and PROPER books obtained from (proper.menlhk.go.id) and the hypothesis is tested using panel data regression analysis. The results of this study indicate that disclosure of carbon emissions has a positive effect on firm value. While environmental performance has no effect on firm value, disclosure of carbon emissions and environmental performance has a positive effect on firm value